The association between dolutegravir-based antiretrovirals and high blood pressure among adults with HIV in southern Ethiopia: a cross-sectional study - Agete Tadewos Hirigo; Daniel Yilma; Ayalew Astatkie; Zelalem Debebe (Therapeutic Advances in Infectious Disease)
Background: Dolutegravir (DTG), a novel antiretroviral therapy (ART) for HIV, is increasingly adopted across sub-Saharan Africa. However, its impact on blood pressure in Ethiopia remains unclear, highlighting a need for further studies. Objective: This study aimed to investigate the association between DTG-based first-line regimens and other covariates of high blood pressure (HBP) among adults living with HIV receiving care at health facilities in Hawassa City, southern Ethiopia. Design: A cross-sectional study. Methods: Data were collected between January 2023 and May 2024 among 444 systematically selected adults, complemented with a review of their medical records. HBP was defined according to the seventh report of the Joint National Committee (JNC7) guidelines, with a threshold of systolic or diastolic blood pressure of ⩾120/80 mmHg. Multivariable logistic regression analysis was performed to identify predictors of HBP. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were computed to determine statistically significant associations. Results: Of the study participants, 58.3% were women and 41.7% were men, resulting in a response rate of 95.5%. The mean (standard deviation (SD]) age of the participants was 38.4(±8.9) years. The prevalence of HBP was 57.9% (95% CI: 52.5–62.4), with 40.5% classified as prehypertension and 17.3% as hypertension. Among participants with hypertension, 84.4% were newly diagnosed. Initiating ART with DTG-based regimens was associated with higher odds of HBP (AOR 5.9; 95% CI: 1.5–22.7) and switching to DTG-based regimens also increased the odds of HBP (AOR 3.8; 95% CI: 1.1–13.9). Other significant covariates associated with HBP included being male (AOR 2.6; 95% CI: 1.4–4.9), age >45 years (AOR 2.0; 95% CI: 1.2–3.4), high waist-to-height ratio (AOR 2.4; 95% CI: 1.1–4.9), inadequate vegetable intake (AOR 1.7; 95% CI: 1.0–2.7), low physical activity (AOR 2.4; 95% CI: 1.1–5.4), and LDL-cholesterol (AOR 1.1; 95% CI: 1.0–1.2). Conclusion: Proactive blood pressure screening and management are important for individuals on DTG-based regimens. In addition, early identification and intervention of modifiable risk factors through comprehensive strategies and regular screenings are pivotal for improving cardiovascular health among individuals on ART.